Srem and Its Volunteers in World War One - Konjević, Branislava R.; Dobrosavljević, Danica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The Serbs from Southern Hungary had been loyal to the official Austro-Hungarian authorities up to the beginning of the 20th century. However, having Serbia stand in the way of the political and military interests of Austria-Hungary and Germany, the treatment of the Serbs deteriorated. Austrian war party asked for a confrontation and encouraged Emperor Franz Joseph to start a war on Serbia. On the accusations of the Sarajevo assassination, Serbia was invaded on July 28, 1914. Following the declaration of the war, Austro-Hungarian authorities shut down most of the Serbian representative bodies and cultural and educational institutions. Leading public figures were interned, while most of the magazines were banned. At the beginning of September, Serbian army entered Srem. Even though short-lived, Serbian offensive sparked hope among the Serbs in Austria-Hungary that the final moment of liberation and unification is on the horizon. The Serbs living at the very border were especially delighted. By the decision of the Supreme Command of Austro-Hungarian army, a mobile court-martial had been installed and on September 11 started operating in Srem, aiming to silence the Serbian population. Austro-Hungarian command sent punitive expeditions to all the settlements where Serbian army had marched through. Large number of Serbs was shot or hanged. Beside torching the houses, sending residents to concentration camps, and looting, Austria-Hungary undertook a complete expulsion of the residents of the Lower Srem. The residents of twenty-seven villages were completely expelled in that region. Churches and schools were demolished and burned, while Fenek Monastery was burned down to the grounds. Large number of Serbs was unwillingly mobilized into Austro-Hungarian army and sent to the Serbian and Russian fronts. A portion of Serbian residents from Srem crossed the Sava River and voluntarily joined Serbian army, aiming to support the struggle of Serbia to liberate the Serbian people from the Austro-Hungarian occupation. Subsequently, the Serbs – former Austro-Hungarian soldiers captured in the battles in Serbia and Russia joined them. Therefore, military volunteers played highly important role in the military activities of the Serbian army. The influx of volunteers was getting higher after the repercussions of the Austro-Hungarian authorities towards the Serbs, their vassals. The data on Srem volunteers in the Serbian army is scarce and mostly accessible through the memories of the participants themselves. Srem Volunteer Unit was officially named so in May 1915, but it had been formed before. Following the Battle of Cer, Serbian units launched an offensive to Srem. During the retreat of the army, many residents of Srem followed, wishing to join the Serbian army. Initially, they were rejected, until luckily coming across Ignjat Kirhner, a defected Austro-Hungarian officer, who also started his military career in the Serbian army as a volunteer. At his insistence, thirty of them became volunteers, and then the number increased. They were mostly underage young men, without any war experience. Ada Ciganlija was turned into field training area for volunteers. The Supreme Command approved forming Srem Volunteer Unit from the volunteers trained at the river islands of Sava. It officially started its military activities under that name on June 1, 1915. Out of all dates related to the cavalry of Belgrade, October 6 takes special place. On that day, enemy forces had managed to reach the Serbian coast and jeopardize Belgrade. The combatants of Srem Volunteer Unit especially stood out among the defenders of Belgrade. In the assault, which followed the famous speech of Major Dragutin Gavrilović, many volunteers gave their lives defending the honour of Belgrade. In the evening hours of October 8, 1915 Srem Volunteer Unit ceased to exist. Out of 340 young men, 223 were killed, while the others were transferred to other units and continued with military activities
Keywords: Srem; volunteers; army; morale; World War One